Gambaran Pengetahuan Dasar Tentang Kriteria Seleksi Donor Pada Mahasiswa Kampus Megarezky, Makassar - Ririn Feriana Basri; Dahniar Dahniar (SEHATI: Jurnal Kesehatan, 2024)
Selection criteria for donors are important to know before conducting blood donation activities. The purpose of this research is to describe the level of basic knowledge of donor selection criteria among students at Megarezky Makassar campus. This research is a descriptive study aimed at describing the percentage of basic knowledge of blood donor selection criteria among students at Megarezky campus. Data were obtained through a questionnaire distributed via Google Forms. The research was conducted in June 2024. The sample size in this research was 65 students from Megarezky Health Polytechnic and Megarezky University. The data were analyzed using SPSS data processing application. Descriptive analysis results from the 65 student respondents in this research show that the majority were female, 46 (70.8%), while the males were 19 (29.2%). The donor selection criteria include age, blood type, and knowledge level. Regarding the distribution of students' knowledge levels related to donor selection criteria, all respondents had good knowledge. Knowledge can be influenced by two factors: internal factors such as education level, occupation, and age, and external factors such as environment and culture. Future research should conduct further studies to understand the knowledge about blood donation and the interest in donating among students.